The Effectiveness of Criminal Sanctions in Defamation Cases Through Social Media Under the Indonesian Criminal Code and the Electronic Information and Transactions Law - Yayan Febriansa; Desy Maryani; Sandi Aprianto (Journal of Law, Social Science, and Management Review, 2026)
The rapid growth of social media as a digital public sphere has significantly increased the occurrence of defamation offenses with broad and immediate impacts. In Indonesia, defamation is regulated under the Criminal Code (KUHP) as well as Law Number 11 of 2008 concerning Electronic Information and Transactions, as amended by Law Number 19 of 2016 (EIT Law). However, in practice, the enforcement of these legal instruments has generated debate regarding their effectiveness, legal certainty, and the balance between the protection of reputation and freedom of expression. This research aims to analyze the regulation and effectiveness of criminal sanctions imposed on perpetrators of defamation through social media. The study employs normative legal research using statutory and conceptual approaches. The findings indicate that although the existing regulations provide a legal basis for enforcement, there remains potential overlap between the Criminal Code and the EIT Law, which affects legal certainty. Furthermore, the effectiveness of criminal sanctions is influenced by legal substance, law enforcement structures, and legal culture within society. Therefore, regulatory harmonization and a proportional approach are necessary to ensure that criminal sanctions create deterrent effects while safeguarding responsible freedom of expression.